2020
DOI: 10.3389/fmars.2020.00109
|View full text |Cite
|
Sign up to set email alerts
|

Using Satellite AIS to Analyze Vessel Speeds Off the Coast of Washington State, U.S., as a Risk Analysis for Cetacean-Vessel Collisions

Abstract: Most species of whales are vulnerable to vessel collisions, and the probability of lethality increases logistically with vessel speed. An Automatic Identification System (AIS) can provide valuable vessel activity data, but terrestrial-based AIS has a limited spatial range. As the need for open ocean monitoring increases, AIS broadcasts relayed over earth-orbiting satellites, satellite AIS (SAIS), provides a method for expanding the range of AIS broadcast reception. We used SAIS data from 2013 and 2014 to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…And, at the same time, the higher density of animals can also impose higher collision risk to the ships navigating in the area (Carrillo et al, 2010). On the other hand, the fine detail of the whale distribution obtained using AIS methodology, could be useful to define and enforce more precise low-speed areas to reduce collisions (Silveira et al, 2013;Greig et al, 2020), which has been identified as one of the measures to reduce the ship strikes in the region (Carrillo et al, 2010). In that sense,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, at the same time, the higher density of animals can also impose higher collision risk to the ships navigating in the area (Carrillo et al, 2010). On the other hand, the fine detail of the whale distribution obtained using AIS methodology, could be useful to define and enforce more precise low-speed areas to reduce collisions (Silveira et al, 2013;Greig et al, 2020), which has been identified as one of the measures to reduce the ship strikes in the region (Carrillo et al, 2010). In that sense,…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its original goal, the enormous AIS data available has proved to be a valuable source of information on human use of marine areas. As a consequence, it has been used for different purposes; from monitoring fishing activity and protected area regulation compliance (Natale et al, 2015;de Souza et al, 2016;Rowlands et al, 2019), to evaluate cetacean-vessel collision risks (Greig et al, 2020), but never before to evaluate whale watching effort. The aim of this study is to evaluate the potential use of AIS data, combined with an open source Digital Terrain Model (DTM), to automatically measure the whale watching effort on a specific region.…”
mentioning
confidence: 99%
“…Risk-modeling studies have illustrated the vulnerability of whales (e.g. blue, fin, killer, and humpback whales) in port entrances with a high ship volume and in areas of substantial coastal (alongshore) traffic (Williams & O'Hara 2010, Redfern et al 2013, Rockwood et al 2017, Greig et al 2020. More than 10 000 transits per year were recorded at the ports of Vancouver, Seattle, and Tacoma, combined (Nichol et al 2017) where vessel strikes are a clear risk to whales (Douglas et al 2008) (Fig.…”
Section: Risk From Commercial Shippingmentioning
confidence: 99%
“…Future research is needed to better understand these risk factors in the context of the Pacific Arctic sector, including the Aleutian Islands, and to better quantify the spatiotemporal distribution of environmental impacts. A handful of studies have been used to assess species-specific vulnerability (Hauser et al, 2018;Greig et al, 2020), and integrating these novel approaches with AIS data holds great promise.…”
Section: Marine Ecology Risk Mitigationmentioning
confidence: 99%